Proceedings of the የአማርኛ ቋንቋ ትምህርት አሰጣጥ በጀርመን አገር—ዓውደጥናት/Workshop: Amharisch Unterrichten in Deutschland/Workshop on the Teaching of Amharic in Germany 1–2 February 2018, Hiob-Ludolf-Zentrum für Äthiopistik, Asien-Afrika-Institut,Hamburg - Krzyżanowska , Magdalena (Aethiopica, 2019)
Conference Report: Proceedings of the የአማርኛ ቋንቋ ትምህርት አሰጣጥ በጀርመን አገር—ዓውደጥናት/Workshop: Amharisch Unterrichten in Deutschland/Workshop on the Teaching of Amharic in Germany 1–2 February 2018, Hiob-Ludolf-Zentrum für Äthiopistik, Asien-Afrika-Institut,Hamburg